Secondary ion mass spectrometry : an introduction to principles and practices - Van der Heide, Paul, 1962- (Hoboken, New Jersey : Wiley, 2014)
"This is presented in a concise yet comprehensive manner to those wanting to know more about the technique in general as opposed to advanced sample specific procedures/applications"--
Chapter 1. Introduction: 1.1 Matter and the Mass Spectrometer ; 1.2 Secondary Ion Mass Spectrometry ; 1.3 Summary -- Chapter 2. Properties of atoms, ions, molecules and solids: 2.1 The Atom ; 2.2 Electronic structure of atoms and ions -- Chapter 3. Current understanding of sputtering and ion formation: 3.1 The fundamentals of SIMS ; 3.2 Sputtering ; 3.3 Ionization/neutralization ; 3.4 Summary -- Chapter 4. Instrumentation: 4.1 The science of measurement ; 4.2 Hardware -- Chapter 5. Data collection: 5.1 The art of measurement ; 5.2 Sample preparation and handling ; 5.3 Data collection ; 5.4 Data conversion -- Appendix i) Periodic table of the elements ; ii) Isotope masses, natural isotope abundances, atomic weights and mass densities of the elements ; iii) 1st and 2nd Ionization potentials and electron affinities of the elements ; iv) Work-functions of elemental solids ; v) SIMS detection limits of selected elements ; vi) Charged particle beam transport ; vii) Statistical properties ; viii) SIMS instrument designs ; ix) Additional SIMS methods of interest ; x) Additional spectrometric/spectroscopic techniques ; xi) Additional microscopic techniques ; xii) Diffraction / reflection techniques -- Technique acronym list -- Abbreviations commonly used in SIMS.
Includes bibliographical references and index.
Machine generated contents note: Forward x Preface xi Acknowledgements xiv List of physical constants xiv Chapter 1: Introduction 1.1 Matter and the Mass Spectrometer 1.2 Secondary Ion Mass Spectrometry 1.3 Summary Section I Chapter 2: Properties of atoms, ions, molecules and solids 2.1 The Atom 2.2 Electronic structure of atoms and ions 2.3 Summary Chapter 3: Current understanding of sputtering and ion formation 3.1 The fundamentals of SIMS 3.2 Sputtering 3.3 Ionization/neutralization 3.4 Summary Section II Chapter 4: Instrumentation 4.1 The science of measurement 4.2 Hardware 4.3 Summary Chapter 5: Data collection 5.1 The art of measurement 5.2 Sample preparation and handling 5.3 Data collection 5.4 Data conversion 5.5 Summary Appendix i) Periodic table of the elements ii) Isotope masses, natural isotope abundances, atomic weights and mass densities of the elements iii) 1st and 2nd Ionization potentials and electron affinities of the elements iv) Work-functions of elemental solids v) SIMS detection limits of selected elements vi) Charged particle beam transport vii) Statistical properties viii) SIMS instrument designs ix) Additional SIMS methods of interest x) Additional spectrometric/spectroscopic techniques xi) Additional microscopic techniques xii) Diffraction / reflection techniques Technique acronym list Abbreviations commonly used in SIMS Glossary of terms Questions and answers References Index Notes .
Description based on print version record and CIP data provided by publisher.
Keywords: Secondary ion mass spectrometry; SCIENCE / Chemistry / Analytic; Secondary ion mass spectrometry; Electronic books; Electronic books